The Munich Pinacotheca in the Private Collection of the Counts Stroganov as Both an Object and a Subject of Intercultural Transfer. (2nd July 2020) - Dashevskaya, Olga A.; Poplavskaya, Irina A.; Ablogina, Evgeniia V.
ABSTRACT: The paper aims to study The Munich Pinacotheca, a graphic collection from the library owned by the Stroganov family and now housed in The Research Library of Tomsk State University, as a universal communicative model of the culture of the eighteenth and nineteenth centuries. Its engravings, made by Ferdinand Piloti and Joseph Löhle, demonstrate structural and thematic integrity. Firstly, it is a general theme of Jesus's Crucifixion based on the following motifs: the Mocking of Christ, his crowning with thorns, the Way of the Cross, deposition and lamentation over the dead Christ, his Ascension and reuniting with God the Father, his Resurrection and Baptism. Secondly, national images of the world, in particular found in the Dutch and the Flemish collections, and paintings featuring the German world. Thirdly, particular types of genre paintings distinguished within the collection.